The world of Matisse, 1869-1954 - Russell, John (Netherland Time-Life International (Nederland) B.V., 1972)
Henri Matisse was schooled as a lawyer, and did not take up art seriously until his early twenties. But when he did, he pursued his training with the logic and determination of an attorney defending a client. He was sure of what he wanted to do, and he was not afraid to express opinions. On his first morning at the Ecole des Beaux-Arts in Paris, he strode into class with his hat on. When his annoyed teacher objected, Matisse is supposed to have calmly informed him, "I'll take it off as soon as you shut the window. There is a strong draft in here."

Such a demonstrably self-assured man would seem to be equally certain of his artistic goals. But it took Matisse many torturous years to develop his own style. Under the guidance of his teacher Gustave Moreau, at the Beaux-Arts, he gained the fundamentals of drawing and composition; by examining Impressionist paintings he came to understand the intense feeling pure color could convey; from his study to Cezanne he learned that a painting must be solidly constructed. These revelations were the results of years of keen observation and wearying toil--years during which the despairing artist was often on the brink of abandoning painting. Matisse copied museum works, experimented with different styles and wrestled with the concepts of the masters and the moderns. From this quest a new and vital art emerged--an art that appeared deceptively simple, but one that only a passionately dedicated man could have created.
Includes bibliographical references and index
FA-3634g - Donated by Carmela Cruz
Keywords: Matisse, Henri; Artists; Artists -- France -- Biography